Simulating the characteristics of tropical cyclones over the South West Indian Ocean using an adaptive Stretched-Grid Global Climate Model - Maoyi, Molulaqhooa Linda (Department of Environmental and Geographical Science, 2016)
Tropical Cyclones are one of the most devastating natural phenomena. Previous attempts to simulate Tropical Cyclones (TCs) over the South West Indian Ocean (SWIO) have used Global Circulation Models (GCMs) with uniform grid. This study examines the capability of a GCM with adaptive grid stretching (CAM-EULAG, hereafter CEU) in simulating the characteristics of TCs over the SWIO. In the study, the CEU model is applied with a fine horizontal grid resolution (0.5°x0.5°) over the SWIO and coarser resolution (1°x1° - 2°x2.25°) over the rest of the globe. The model simulation is performed for 11 years (1999-2010) and validated against the Joint Typhoon Warning Centre (JTWC) best track observation, Global Precipitation Climatology Project (GPCP) satellite data, and ERA-Interim (ERAINT) reanalysis data. The study also considers the impact of El Niño Southern Oscillation (ENSO), Indian Ocean Dipole (IOD) and the South Atlantic Subtropical Dipole (SASD) on TC counts over the SWIO.